PERANAN IBU SINGLE PARENT DALAM PERKEMBANGAN SOSIAL DAN PERILAKU KEAGAMAAN REMAJA DI KELURAHAAN AEK TAMPANG KOTA PADANGSIDIMPUAN - Maslina Daulay, M.A (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2017)
The background of the problems in this research are many young people in Aek Tampang District looked bad attitudes, it seemed from their social development which are more likely can damage the environment, even from the religious aspects, they avoided doing it. The single parent mothers are expected the main cause of the problems, where they are busy in financing their families. The purposes of this research are to find the role of single parent mothers in educating and developing their children, to know the social development of the young people and the religious behaviours, and to identify the effects of economic life to their mental health. It has been done qualitatively, by using interviews and observation as the instruments. Then, analysed it descriptively. The result shows that the single parent mothers are busy to earn money for their families, so, the have less time to handle, to educate, and to control their family. Although they have given their time to educate and controlled them, it looks that their children did not follow their parents. It is also found the young people are easier to be influenced by their environment, by their friends, then by their parents, and it made they also are far from the religious side